Implementation of dynamic compensators in the multi-loop control system - Денисенко, Олексій Юрійович; Козаневич, Звенислава Ярославівна (Technology audit and production reserves, 2016)
This article discussed how to implement dynamic compensators for multi-loop control systems that make up the process control system or computer-integrated systems. The main aim of the study is to validate the choice of a method of technical implementation of dynamic compensators. The characteristics of the considered methods for implementation of dynamic compensators are given. Suitability indicators of these methods are proposed for inclusion in the composition of automated process control systems and/or computer-integrated systems of multi-loop control systems that contain dynamic compensators in their structure. Comparison of the suitability of the methods for the technical implementation of dynamic compensators is considered using the proposed indicators. Specific method of technical implementation of dynamic compensators is chosen as a result of comparison of indicators. The proposed method makes it possible to unify the software elements of dynamic objects control systems. The research results can be applied by experts in the synthesis of elements of software and automated computer-integrated process control systems.